Determination of occupational nuisance dust concentration from the casting room in the public hospital in Kuala Lumpur, Malaysia - Bakar, Z.A.; Kahar, A.W.M.; Rahman, I.A.; Ithnin, A.; Senik, N.S. (2021)
The emergence of dust generated from the process of removal orthopedic cast materials pose a significant potential hazardous to respiratory health among the healthcare workers (HCWs) in the orthopedic casting room. The study was carried out to determine the total dust concentrations in the casting room were exposed to environmental and personnel. The personnel and environmental air sampling were conducted for 6 hours followed the standard method from NIOSH Manual of Analytical Method 0501. Determination of personnel dust exposure were established for selected six HCWs, who are highly risk of dust exposed based on their jobs scope in the casting room. The determination of environmental air sampling was conducted in the casting room for six hours continuously. A set of questionnaires was administered to evaluate the level of knowledge, attitude and practice related to the awareness of occupational safety and health among the 43 HCWs from public hospital in Kuala Lumpur, Malaysia. The result on total dust from the environmental air sampling (casting room) showed mean concentration are 3.402 ± 0.003 mg/m and personal air sampling showed the mean concentration are 5.573± 0.040 mg/m The mean total concentration obtained were below the standard permissible exposure limit of 15 mg/m set by OSHA USA 2005. The result shows the level of knowledge were 96.75%, attitude 83.7% and practical 82.85% among the HCWs. There are significant relationship (p <0.05) level of knowledge with age, job titles and area of workplace. There are significant relationships (p <0.05) level of attitudes with job titles. There are also showed a significant relationship (p <0.05) level of practices with age, job titles and working hour per week. The potential risk of dust exposure to the HCWs in the casting room were manageable because the dust concentration are still low and there are adequate usage of PPE with good functioning exhaust systems in the casting room. Most HCWs have a high level of knowledge, attitude and practical of occupational safety and health. The study showed HCWs in this study are aware of the potential hazard associated with their workplace activities. It is the responsibility of the organization and the HCWs for providing a healthy and safe workplace in accordance with the requirements of the Occupational Safety and Health Act 1994 (Act 514) and relevant regulations.